2004
DOI: 10.1143/jpsj.73.2550
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Dead Layers Induced by Strain at fct Fe/Rh(001) Interface

Abstract: We have studied magnetic properties of face-centered-tetragonal (fct) Fe thin films grown at room temperature on the Rhð001Þ surface. Band structure calculations show that the stable magnetic phase of fct Fe on the Rhð001Þ surface is ferromagnetic (FM), which agrees with our previous conclusion obtained by angle-resolved photoelectron spectroscopy and spin-and angle-resolved photoelectron spectroscopy (SARPES) of the four monolayers (ML) Fe film [K. Hayashi et al.: Phys. Rev. B 64 (2001) 054417]. This magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…For example, no notable intermixing has been encountered at the interface of Fe/Rh(100) during growth of Fe films. 20 Epitaxial, pseudomorphic layer-by-layer growth of one and two layers of Co on Rh(100) was reported by Begley et al, 21 and several groups 20,[22][23][24] have been able to grow pseudomorphically even thicker films of face-centered tetragonal Fe on Rh(100). Recent reports show that FeCo alloys can be grown on Rh(100) where the composition of the alloy can be used to tailor the magnetic anisotropy of the system.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…For example, no notable intermixing has been encountered at the interface of Fe/Rh(100) during growth of Fe films. 20 Epitaxial, pseudomorphic layer-by-layer growth of one and two layers of Co on Rh(100) was reported by Begley et al, 21 and several groups 20,[22][23][24] have been able to grow pseudomorphically even thicker films of face-centered tetragonal Fe on Rh(100). Recent reports show that FeCo alloys can be grown on Rh(100) where the composition of the alloy can be used to tailor the magnetic anisotropy of the system.…”
Section: Introductionmentioning
confidence: 84%
“…With the exception of Ni, in all cases the equilibrium distance between the interface Rh layer and the bulk Rh underneath, d 23 , increases with respect to the substrates' bulk interlayer spacing. Moving from left to right through the periodic table, we find that d 23 decreases, supporting the interpretation that the d-band filling controls these relaxations.…”
Section: A Relaxations and Magnetic Momentsmentioning
confidence: 90%
See 2 more Smart Citations
“…There exist reliable low energy electron diffraction (LEED) measurements (elucidating the detailed geometry) on very thin overlayers grown on Ir substrate with negligible Fe-Ir intermixing [9]. Furthermore, magneto-optical Kerr effect studies found no magnetization of iron overlayers thinner than ≈ 4 monolayers on Ir(001) [9] and ≈ 2 monolayers on Rh(001) [11]. The Fe/Ir system is a good candidate to investigate the magnetic properties of ultrathin films, since both materials grow in a two-dimensional atomic layer- * This paper was presented at 10th International Conference on Atomically Controlled Surfaces, Interfaces and Nanostructures (ACSIN-10), Granada Conference Centre, Spain, 21-25 September, 2009.…”
Section: Introductionmentioning
confidence: 99%